PENGARUH KADAR AIR DI DALAM BRAKE FLUID TERHADAP KARAKTERISTIK GELEMBUNG PADA PROSES PEMANASAN BRAKE FLUID - Wijayanta, Setya; Humami, Faris; Wibowo, Helmi; Kristiawan, Komang Andre; Lazuardi, Wildan Surya (Jurnal Rekayasa Mesin, 2024)
The present study aimed to determine the effect of the percentage of water in brake fluid on the boiling point and the characteristics of bubble formation (the beginning of vapor lock) during the brake fluid heating process. DOT 3 Brake Fluid and water were used as the working fluid in the present study. To vary the water content in the brake fluid, water was mixed into the DOT 3 Brake Fluid. The water percentages in the mixture were 0, 1, 3, and 4%. The boiling point of brake fluid with four variations in the water content percentage was measured by using a digital thermometer. The characteristics of bubble formation in brake fluid were observed using a video camera with a frame rate of 240 fps. The video recording results were extracted into an image file with a jpeg extension and processed further using image processing with ImageJ software to measure the total cross-sectional area and bubble fraction. This is the novelty of the present study, where measurements of the total cross-sectional area and bubble fraction in boiling brake fluid with variations in water content have never been carried out by researchers before. Apart from that, the ImageJ measurement method has advantages compared to other software. ImageJ is free software that is easy to download from the internet, easy to use, accurate and the measurement results are displayed immediately. The research results show that an increase in the percentage of the water content in brake fluid affects reducing the boiling point of the brake fluid. At the same temperature, the greater the percentage of water content in the brake fluid, the total cross-sectional area and bubble fraction also increase. At the same percentage of water content, the total cross-sectional area and bubble fraction also increase as the temperature increases. Apart from that, in this research, an empirical equation was successfully developed to predict the brake fluid's boiling point based on its water content, and an empirical equation to predict the bubble fraction based on the water content and temperature of the brake fluid. This is a novel result of this research that has never been produced in previous research.